STRATEGI KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN ISLAM (Studi Kasus di MAS JAM’IYYAH ISLAMIYYAH Pondok Aren) - Ahmad Masruri (Institut PTIQ Jakarta, 2019)
This study discusses the principal's strategy in improving the quality of Islamic Education in MAS Jam’iyyah Islamiyyah Pondok Aren. The world of education, especially Islamic education, is increasingly faced with quite severe challenges. Because Muslims live in a modern era full of challenges and opportunities. Islamic educational institutions especially madrassas still experience obstacles in improving the quality of education. This can be seen from various aspects ranging from curriculum objectives, education personnel, learning methodology, infrastructure, and evaluation, as a whole still contains problems that have yet to be completely resolved. For this reason, improving the quality of Islamic education in madrasas requires strong leadership from the principal. The purpose of this study was to evaluate: 1) the principal's efforts to improve teacher professionalism, 2) the principal's efforts to improve the quality of educational infrastructure, 3) the principal's efforts to improve the quality of the learning process, and 4) the principal's efforts to improve student achievements at MAS Jam'iyyah Islamiyyah Pondok Aren. This research uses a descriptive-qualitative method and approach using three research instruments, namely interviews, observations, and documentation studies. The results showed that: 1) MAS Jam’iyyah Islamiyyah Pondok Aren has experienced good quality improvement. Under the leadership of a reliable school principal, MAS Jam’iyyah Islamiyyah Pondok Aren can now be one of the institutions of Islamic education that is in the vanguard and capable of producing outputs that excel. 2) The principal's efforts in improving the quality of education, namely: a) increasing teacher professionalism by creating rules for teachers, placing teachers according to their abilities, giving confidence and motivation, conducting coaching. b) improve the quality of infrastructure facilities through improving infrastructure, collaborating with other institutions / agencies in the procurement of infrastructure. c) improve the quality of the learning process by developing Islamic education models, improving learning methods, managing curriculum quality. d) improve student achievement by holding activities of strengthening, additional lessons, collaboration with tutoring institutions, guiding teachers to create effective learning, creating a disciplined school culture, providing various extracurricular activities, sending students in various competitions.